Public perceptions of adult ADHD: indications of stigma? - Godfrey, Emmet; Fuermaier, Anselm B. M.; Tucha, Lara; Butzbach, Marah; Weisbrod, Matthias; Aschenbrenner, Steffen; Tucha, Oliver (Journal of neural transmission, 2021)
Stigmatization represents a major barrier to treatment seeking across mental disorders. Despite this, stigma research on individual mental disorders remains in its infancy. Attention-deficit hyperactivity disorder (ADHD) in adults also represents an under-researched area—being far less studied than its child counterpart. This study examined the current state of public perceptions towards adult ADHD. A simulation group consisting of 105 participants performed the Weiss Functional Impairment Rating Scale (WFIRS) and Conners’ Adult ADHD Rating Scales (CAARS) as though they had ADHD. These scores were compared to a group consisting of 98 individuals with adult ADHD and a group of 117 healthy individuals both groups being instructed to complete the WFIRS and CAARS to the best of their abilities. Simulators were found to overestimate impairments in adult ADHD (to a large effect) in the domains of hyperactivity, DSM-IV hyperactivity-impulsivity, DSM-IV total, work, school, (to a medium effect) in family and social, and (to a negligible-small effect) in inattention, impulsivity, DSM-IV inattention, and life skills when compared to the ADHD group, and in all domains (to a large effect) when compared to the control group. Current and retrospective ADHD symptoms were found to be associated with more accurate perceptions in a number of domains. Evidence for the presence of perceptions considered to be stigmatizing was found, with largest effects present in the domains of hyperactivity, impulsivity, impairments at work, school, and engagement in risky behaviour.